2012
DOI: 10.1115/1.4006710
|View full text |Cite
|
Sign up to set email alerts
|

Soot Evolution With Cyclic Crank-Angle-Resolved Two-Color Thermometry in an Optical Diesel Engine Fueled With Biodiesel Blend and ULSD

Abstract: Biodiesel is a desirable alternative fuel for the diesel engine due to its low engine-out soot emission tendency. When blended with petroleum-based diesel fuels, soot emissions generally decrease in proportion to the volume fraction of biodiesel in the mixture. While comparisons of engine-out soot measurements between biodiesel blends and petroleumbased diesel have been widely reported, in-cylinder soot evolution has not been experimentally explored to the same extent. To elucidate the soot emission reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…scale=0.8 soot temperature and soot KL factor could therefore be potentially attributed to the occurrence of enhanced soot oxidation in the low soot temperature and KL zones, leaving the average temperature and soot KL factor to be dominated by the soot signal from the local high temperature and soot concentration regions [29]. Focusing on quasi-steady periods for the flames, prior to the end of injection, it can be seen that a decrease in the ambient O 2 condition did not appear to significantly impact on the average soot temperature and soot KL factor values of the flames, until it was reduced to 10 vol.% O 2 .…”
Section: Soot Temperature and Soot Kl Factormentioning
confidence: 99%
“…scale=0.8 soot temperature and soot KL factor could therefore be potentially attributed to the occurrence of enhanced soot oxidation in the low soot temperature and KL zones, leaving the average temperature and soot KL factor to be dominated by the soot signal from the local high temperature and soot concentration regions [29]. Focusing on quasi-steady periods for the flames, prior to the end of injection, it can be seen that a decrease in the ambient O 2 condition did not appear to significantly impact on the average soot temperature and soot KL factor values of the flames, until it was reduced to 10 vol.% O 2 .…”
Section: Soot Temperature and Soot Kl Factormentioning
confidence: 99%
“…A novel color band approach, which was first introduced by Larsson 30 and further expanded upon by Svensson et al 31 was implemented to provide soot temperature and soot KL (a factor that is proportional to the soot volume fraction and gas layer thickness 31,32 ) information.…”
Section: Flame Luminosity Imaging Post-processingmentioning
confidence: 99%
“…Following the approach of Zha et al, 32 to reduce the computational time during image processing, two universal surfaces ( Fig. 5) that map the domains of the red and green pixel intensities to soot temperature and KL surfaces, were generated.…”
Section: Flame Luminosity Imaging Post-processingmentioning
confidence: 99%
“…Zha et al . performed in‐cylinder soot evolution studies in an optical diesel engine fueled with B20 biodiesel blend and ultra‐low sulfur diesel. It was observed that B20 had more splashing during spray wall impingement and shorter ignition delay and combustion duration than diesel.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the presence of methyl or ethyl functional group resulted in reducing the sooting propensity compared to n-alkanes, caused by both thermal and kinetic mechanisms. Zha et al [17] performed in-cylinder soot evolution studies in an optical diesel engine fueled with B20 biodiesel blend and ultra-low sulfur diesel. It was observed that B20 had more splashing during spray wall impingement and shorter ignition delay and combustion duration than diesel.…”
Section: Introductionmentioning
confidence: 99%